2008
DOI: 10.1161/circulationaha.106.685073
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Angiotensin-Converting Enzyme Inhibition in Low-Risk Patients Early After Coronary Artery Bypass Surgery

Abstract: Background-Early after coronary artery bypass surgery (CABG), activation of numerous neurohumoral and endogenous vasodilator systems occurs that could be influenced favorably by angiotensin-converting enzyme inhibitors. Methods and Results-The Ischemia Management with Accupril post-bypass Graft via Inhibition of the coNvertingEnzyme (IMAGINE) trial tested whether early initiation (Յ7 days) of an angiotensin-converting enzyme inhibitor after CABG reduced cardiovascular events in stable patients with left ventri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(68 citation statements)
references
References 20 publications
0
65
1
2
Order By: Relevance
“…797 Similarly, the IMAGINE (Ischemia Management With Accupril Post-Bypass Graft via Inhibition of the Converting Enzyme) study demonstrated no reduction in clinical outcomes in low-risk patients (LVEF Ͼ40%) with quinapril after surgical revascularization. 803 In a meta-analysis of ACE-inhibitor therapy versus placebo in 31 555 patients from HOPE, EUROPA, PEACE, and QUIET, ACE-inhibitor therapy produced 14% reductions in all-cause mortality and MI (both Pϭ0.0004), a 23% reduction in stroke (Pϭ0.0004), and a 7% reduction in revascularization procedures (Pϭ0.025) compared with placebo. 796 Although the cited studies involved a variety of ACE inhibitors that differ with regard to structure, bioavailability, potency, receptor-binding characteristics, tissue distribution, metabolism, and excretion properties, there is little evidence that these differences are associated with therapeutic advantages.…”
Section: Fihn Et Al Stable Ischemic Heart Disease: Full Text E405mentioning
confidence: 99%
“…797 Similarly, the IMAGINE (Ischemia Management With Accupril Post-Bypass Graft via Inhibition of the Converting Enzyme) study demonstrated no reduction in clinical outcomes in low-risk patients (LVEF Ͼ40%) with quinapril after surgical revascularization. 803 In a meta-analysis of ACE-inhibitor therapy versus placebo in 31 555 patients from HOPE, EUROPA, PEACE, and QUIET, ACE-inhibitor therapy produced 14% reductions in all-cause mortality and MI (both Pϭ0.0004), a 23% reduction in stroke (Pϭ0.0004), and a 7% reduction in revascularization procedures (Pϭ0.025) compared with placebo. 796 Although the cited studies involved a variety of ACE inhibitors that differ with regard to structure, bioavailability, potency, receptor-binding characteristics, tissue distribution, metabolism, and excretion properties, there is little evidence that these differences are associated with therapeutic advantages.…”
Section: Fihn Et Al Stable Ischemic Heart Disease: Full Text E405mentioning
confidence: 99%
“…The IMAGINE (Ischemia Management With Accupril Post Bypass Graft via Inhibition of Angiotensin Converting Enzyme) study failed to show a beneficial effect of postoperative ACE inhibitor therapy 3 years after CABG, instead noting an increase in adverse events, particularly recurrent angina in the first 3 months of therapy. 630 A subanalysis of the data from patients enrolled in EUROPA (European Trial on the Reduction of Cardiac Events with Perindopril in Stable Coronary Artery Disease) with previous revascularization (CABG or PCI no sooner than 6 months before enrollment) suggested a primary and secondary prevention benefit over a 4.2-year follow-up period; however, an analysis of the data from almost 3000 patients in the PREVENT IV (PRoject of Ex-vivo Vein graft ENgineering via Transfection) trial, all of whom were taking either ACE inhibitors or ARBs at the time of hospital discharge, failed to demonstrate a significant reduction in death or MI after 2 years of follow-up in "ideal" candidates (based on ACCF/AHA/HRS guidelines) (HR: 0.87; 95% CI: 0.52 to 1.45; PϭNS), whereas significance was achieved in "non-ideal" candidates (HR: 1.64; 95% CI: 1.00 to 2.68; Pϭ0.05). Smoking cessation after CABG is associated with a substantial reduction in subsequent MACE, including MI and death.…”
Section: Cabg In Patients With Hypothyroidismmentioning
confidence: 99%
“…The incidence of the primary composite end point increased significantly in the first 3 months after CABG in the quinapril group (P=0.04), and adverse events (such as hypotension) were also increased in the quinapril group, particularly during the first 3 postoperative months. 233 Thus, in this select trial population, routine ACE inhibitor therapy led to more harm than benefit when initiated early after CABG.…”
Section: Hypertension Managementmentioning
confidence: 96%
“…[244][245][246] The routine initiation of an ACE inhibitor early after CABG is not recommended for patients with an EF >40%. 233 However, it is unlikely that surgical revascularization mitigates the benefits of an ACE inhibitor in the post-CABG patient with a persistently reduced EF.…”
Section: Ace Inhibitor and Arb Therapymentioning
confidence: 99%